What do young Australian engineers want? Strategies to attract this talent to less glamorous industries - Wallace, M.; Sheldon, N.; Cameron, Roslyn; Lings, I. (Springer, 2014)
Chapters in Book 1 of this two-volume set explored literature pertaining to the shortage of engineers in Australia, the ageing engineering workforce, issues of skilled migration, and career development and pathways. The companion chapter to this one in Book 1 explored attraction and image issues of certain industries that required a pipeline of engineers. This chapter will reflect on our research with final- year engineering students in Australian universities and TAFE colleges regarding their career aspirations, industries and/or organisations that they identify as attractive employers, and their perceptions of a low-profile industry, namely the Australian rail industry. This chapter will also discuss specific, evidence-based strategies and activities to enhance the image and attraction of low-profile industries.